If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 7v + 26 Reorder the terms: 0 = 26 + 7v Solving 0 = 26 + 7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-7v' to each side of the equation. 0 + -7v = 26 + 7v + -7v Remove the zero: -7v = 26 + 7v + -7v Combine like terms: 7v + -7v = 0 -7v = 26 + 0 -7v = 26 Divide each side by '-7'. v = -3.714285714 Simplifying v = -3.714285714
| ln(x)+2=0 | | -8=t-2 | | 4(4x-2.2)=2x-8.8 | | 7(1+2a)=-105 | | 22x+13=-18x+13 | | ln(2x+1)ln(9-4x)=0 | | ln(2x-1)ln(9-4x)=0 | | 7(x-7)=-98 | | x+4=x-9 | | 17=-6v-2 | | -6=-8m+8-6 | | -(3m-8)=12-m | | -5n+6n=2 | | 5m-4m=8 | | -2x+8x=-18 | | 9=-12t+3 | | 5y-6=2y-30 | | a+b=21 | | -13=-2y+7 | | -12t-3=9 | | -(3m-8)=13-m | | 6(x-3)+3=2x+4(-3+x) | | 3(4x-6)=2(6x+3) | | (-8x-5)=(-2-7x) | | 2x+[2x-(x-4)]=-[-(5-x)] | | 8x-3(2x-3)=-4(2-x)+3(x-4)-1 | | 6(x-3)=3+6x+3x | | 4x-17=3x-12 | | 9-5(3a+5)= | | y-7.34=9.06 | | y=x+1.75 | | 0=3z+26 |